Fiber tip Michelson interferometer for temperature sensing based on polymer-filled suspended core fiber. (September 2021) - Wang, Shun; Yang, Yaowen; Niu, Panting; Wu, Shun; Liu, Shuhui; Jin, Rui-Bo; Lu, Peixiang; Hu, Xiongwei; Dai, Nengli
Highlights: Low-cost fiber MI temperature sensor is formed by filling SCF with polymer-UV glue. High sensitivity is obtained due to the great thermal properties of UV glue. Our sensor shows advantages of robust, small size, and low cost. The reflective tip structure enable for remote sensing in practical applications. Abstract: A low-cost fiber tip temperature sensor is proposed and experimentally demonstrated. It is based on the Michelson interferometer (MI) structure which is partially filled with polymer-UV glue in the suspended core fiber (SCF). Due to the greater thermal properties of UV glue compared with the silica optical fiber, the length of the inner cavity in the MI structure is susceptible to temperature modulation, resulting in the interference wavelength drift. Experimental results show that the sensor achieves a sensitivity of −164 pm/°C in the temperature range of 25–60 °C, and the sensor offers good wavelength and power stability at room temperature. In addition, the sensor has advantages such as robust, small size, and low cost, especially the reflective tip structure is more suitable for remote sensing in practical applications.